INVENTARISASI TUMBUHAN OBAT DALAM PENGOBATAN TRADISIONAL MASYARAKAT KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA TAHUN 2023 - SARI, DINA YUSPITA; Utami, Kurnia Dwi (Jurnal Komunitas Farmasi Nasional, 2023)
Most of the people of West Kalimantan use traditional medicinal plants for treatment. Kubu Raya Regency is one of the districts that has traditional medicine (Battra), which uses medicinal plants in its practice. This research aims to carry out an inventory of medicinal plants used by traditional healers in Batra. The research design used in this research is descriptive research. The method used was to observe Batra to obtain information, followed by interviews. The data analysis technique used is qualitative in the form of narrative analysis, where data is obtained from traditional healers and then described to find out the names, properties, parts used, and methods of making and using medicinal plants. From the research results, it was found that 12 types of medicinal plants were used by traditional healers, namely alang-alang roots, cat's whisker leaves, guava leaves, Euphorbia tirucalli leaves, pegagan leaves, bay leaves, buas-buas leaves, white cumin, tapak jala leaves, cengkodok leaves, red betel leaves, and turmeric. The parts of the plant used are roots, rhizomes, leaves, and seeds. The way to make and use medicinal plants is by pasting, smearing, or smearing them. Some diseases treated using medicinal plants include fever, toothache, high blood pressure, blood sugar, itching, fungus, scabs, diarrhea, ulcers, rheumatism, hemorrhoids, stomach aches, low back pain, burns, irritated wounds, and skin inflammation.